2004
DOI: 10.1074/jbc.m403541200
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Resolution Structures and Solution Behavior of Enzyme-Substrate Complexes of Enterobacter cloacae PB2 Pentaerythritol Tetranitrate Reductase

Abstract: The structure of pentaerythritol tetranitrate (PETN) reductase in complex with the nitroaromatic substrate picric acid determined previously at 1.55 Å resolution indicated additional electron density between the indole ring of residue Trp-102 and the nitro group at C-6 of picrate. The data suggested the presence of an unusual bond between substrate and the tryptophan side chain. Herein, we have extended the resolution of the PETN reductase-picric acid complex to 0.9 Å. This high-resolution analysis indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 21 publications
2
51
0
1
Order By: Relevance
“…[16] The co-crystal structures of wild-type PETN reductase and mutants W102F and W102Y complexed with picric acid were determined previously. [30] A comparison of the structures showed no major structural changes, however, the conversion of W102 to phenylalanine removed the hydrogen bond between W102 NE1 and Q60 NE2 present in the wild-type structure. [24] Solution studies indicated that picric acid was bound more tightly to the active site of the two mutant enzymes, with no significant impairment of FMN reduction by NADPH.…”
Section: Biotransformations With Confirmed Mutantsmentioning
confidence: 97%
“…[16] The co-crystal structures of wild-type PETN reductase and mutants W102F and W102Y complexed with picric acid were determined previously. [30] A comparison of the structures showed no major structural changes, however, the conversion of W102 to phenylalanine removed the hydrogen bond between W102 NE1 and Q60 NE2 present in the wild-type structure. [24] Solution studies indicated that picric acid was bound more tightly to the active site of the two mutant enzymes, with no significant impairment of FMN reduction by NADPH.…”
Section: Biotransformations With Confirmed Mutantsmentioning
confidence: 97%
“…Expression of pentaerythritol tetranitrate reductase in tobacco (Nicotiana tabacum) confers both resistance to, and the ability to transform, TNT (French et al, 1999). OPR1, OPR2, and OPR3 share 43%, 44%, and 36% identity, respectively, with pentaerythritol tetranitrate reductase, and all possess the conserved active site amino acids crucial for TNT transformation by pentaerythritol tetranitrate reductase and other members of the Old Yellow Enzyme family (Snape et al, 1997;French et al, 1998;Khan et al, 2004), suggesting that they are capable of transforming TNT.…”
mentioning
confidence: 99%
“…The corresponding residue in PETN reductase plays a major role in directing reactivity against nitroaromatic substrates along nitro reduction and hydride transfer pathways, the latter generating a Meisenheimer⅐hydride complex of the nitroaromatic substrate. High resolution structural studies indicate that in PETN reductase the tryptophan residue adopts multiple conformational states influenced by ligand (nitroaromatic) binding (38). The Meisenheimer⅐hydride pathway for nitroaromatic degradation is restricted to PETN reductase (22,39), prompting the question as to the role of the conserved tryptophan residue in the remaining members of the OYE family.…”
Section: Resultsmentioning
confidence: 99%
“…Our work described in this report has demonstrated that the conserved tryptophan residue in the active site of OYE family members is not essential for the reduction of ␣/␤ unsaturated carbonyl compounds, although in PETN reductase it plays a major role in pathway selection for the degradation of nitroaromatic compounds presumably by influencing the geometry of attack of the hydride ion on the aromatic nucleus of these substrates (38). OYE and MR are known to reduce nitroaromatic substrates, but reduction of these compounds does not proceed through the Meisenheimer reduction pathway (22).…”
Section: Discussionmentioning
confidence: 99%